The possibility of using entomopathogenic nematodes and entomophages as bioagents of the western corn rootworm (Diabrotica virgifera virgifera Le Conte) - Sikura, A.; Gunchak, V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
The article presents the results of studies on the possibility of using entomopathogenic nematodes and entomophages against the western corn rootworm. It is established that the bioagents under study are able to regulate the number of Diabrotica virgifera virgifera Le Conte. The obtained results showed the prospects of using these biological agents for phytophage control.